In the Name of Integrity? Anticorruption Discourse of Brazilian Operation Lava Jato. - Luis Grangeia, Mario; Thijm, Joris Alberdingk (Latin American Research Review, 2025)
This article identifies four frames of corruption in the discourse of three leaders of Operation Lava Jato, also known in English as Operation Car Wash, a large-scale Brazilian anticorruption operation (2014–2021). These frames are inequality, hidden pact, backwardness, and chronic disease. The frames were identified by analyzing a wide set of press interviews, opinion articles, and books by two prosecutors and one judge whose work has revealed scandals involving the state oil company Petrobras. The operation had a major impact on politics and the economy and left a controversial legacy. We noticed a contradiction between one frame invoking judicial activism (inequality) and three frames focusing on specific techniques that appeal to a more conventional view on the judiciary’s role (hidden pact, backwardness, and chronic disease). Furthermore, even when scholars were still largely positive about the operation, the discourse showed signs of judicial activism. This analysis contributes to the debate on Lava Jato and judicial activism by focusing on discourse rather than action.